2015
DOI: 10.3389/fpsyg.2015.01145
|View full text |Cite
|
Sign up to set email alerts
|

When parenting fails: alexithymia and attachment states of mind in mothers of female patients with eating disorders

Abstract: Introduction: In recent years alexithymia and attachment theory have been recognized as two parallel research lines trying to improve the information on the development and maintenance of eating disorders (EDs). However, no research has analyzed these constructs among patients’ families. In this study we compared alexithymia and attachment in mothers of patients with EDs and a control group. Further, we hypothesized that mothers of daughters with EDs with insecure and unresolved states of mind will reported hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 76 publications
(119 reference statements)
4
17
0
Order By: Relevance
“…The specific quality of the attachment to the primary caregivers has been extensively investigated in eating disorders. The data confirm what Bruch describes in her lecture and indicate that both adults (Tasca & Balfour, ; Zachrisson & Skarderud, ) and adolescents (Gander, Sevecke, & Buchheim, ; Jewell et al, ) with anorexia nervosa recall insecure patterns of attachment, often characterised by attachment devaluation or difficulties of processing loss and trauma (Pace, Cavanna, Guiducci, & Bizzi, ). A recent meta‐analysis concluded that the effect for insecure attachment in adult patients is large ( d = 1.3) (Caglar‐Nazali et al, ).…”
Section: Part 1: Bruch's Clinical Observations and Translation Into Csupporting
confidence: 81%
See 1 more Smart Citation
“…The specific quality of the attachment to the primary caregivers has been extensively investigated in eating disorders. The data confirm what Bruch describes in her lecture and indicate that both adults (Tasca & Balfour, ; Zachrisson & Skarderud, ) and adolescents (Gander, Sevecke, & Buchheim, ; Jewell et al, ) with anorexia nervosa recall insecure patterns of attachment, often characterised by attachment devaluation or difficulties of processing loss and trauma (Pace, Cavanna, Guiducci, & Bizzi, ). A recent meta‐analysis concluded that the effect for insecure attachment in adult patients is large ( d = 1.3) (Caglar‐Nazali et al, ).…”
Section: Part 1: Bruch's Clinical Observations and Translation Into Csupporting
confidence: 81%
“…A recent meta‐analysis concluded that the effect for insecure attachment in adult patients is large ( d = 1.3) (Caglar‐Nazali et al, ). Interestingly, a similar pattern of attachment is seen in patients' mothers (Ward et al, ; Pace et al, ).…”
Section: Part 1: Bruch's Clinical Observations and Translation Into Csupporting
confidence: 57%
“…In line with this, lower parental care and higher parental control can be associated with worse personality traits and psychological functioning and stronger ED symptoms (Amianto et al, 2015). Although more studies focus on the mother-child relationship in ED patients (Claydon et al, 2016;Pace et al, 2015), present results also underline the association between the degree of paternal care and the severity of ED symptoms among ED patients. Similarly, Horesh et al (2015) found that patients with overprotective or avoidant paternal bonding presented higher levels of depression and worse eating and body shape concerns (including more severe food-restraint) than those who experienced caring and benevolent father-daughter relationships.…”
Section: Characteristics Of Eating Disorder Patientssupporting
confidence: 81%
“…In line with this suggestion, ED patients suffer from separation anxiety (Troisi et al, 2005) and ED symptoms usually engage parental involvement, decreasing the distance with their parents (Orzolek-Kronner, 2002). Mothers of anorexic females reported themselves low levels of alexithymia, while their daughters perceived high maternal alexithymia (Pace et al, 2015). This hints at the differences in the perception of the degree of emotional responsiveness in ED families.…”
Section: Characteristics Of Eating Disorder Patientsmentioning
confidence: 79%
“…From a clinical perspective, it may be beneficial to consider attachment state of mind assessed by the AAI during the clinical assessment of patients with ED, with and without co-morbidity with BPD, as it may shed light on the ability to engage patients in treatment relationships and also may provide some insight into potential vulnerability for rupture of patient-therapist relationship and better specialized interventions (Dazzi and Zavattini, 2011;Pace et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%